Determination of Favorable Lithofacies for Continental Shale Gas: A Case Study of the Shahezi Formation, Changling Fault Depression, Songliao Basin - Xu, Wen; Yang, Guoqiao; Li, Ang; Song, Zhenxiang; Hu, Wenhui (Frontiers in Earth Science, 2022)
Abstract：In order to determine the optimum lithofacies for continental shale, the reservoir characteristics of different lithofacies types were studied based on a series of experiments，including organic geochemical analysis, X-ray diffraction (XRD) analysis, porosity tests, N2 and CO2 adsorption, high-pressure mercury intrusion porosimetry (MIP) experiments and gas content measurement. According to the results of mineral composition and TOC content, the lacustrine organic-rich shale of Shahezi Formation are divided into siliceous (ORS), argillaceous (ORA), calcareous (ORC) and mixed (ORM) shale. The ORS, ORA, ORC and ORM shale are carried out comprehensive reservoir comparative analysis. The results show that, the moderate content of clay minerals (45%) can significantly improve porosity, high and low clay mineral content is not conducive to the improvement of porosity. The ORM shale tend to have a better pore connectivity than the ORS and ORA shale, and the ORC shale has the poorest pore-throat connectivity in micron-size. The ORM shale may have more irregular surface and lower liquid/gas surface tension. The higher capillary condensation on pore surfaces is more likely to occur in the ORA shale. The ORS shale offer less adsorption sites for CH4 and has lower adsorption capacity. The ORC shale has weak heterogeneity of pore structure. Therefore, the ORM shale may be the most favourable lithofacies for shale gas enrichment and development, which has high porosity, good pore connectivity, moderate brittleness and strong gas adsorbtion and storage capacity, followed by the ORS and ORA shale, the ORC shale is the worst.